Are gas release auctions effective? - Friedel Bolle; Yves Breitmoser (European University Viadrina, Department of Business Administration and Economics, 2006)
European and national cartel authorities have required dominant national gas pipelines to auction off certain quantities (typically about 10 % of their sales) to competitors. Do such auctions really improve the competitiveness of the wholesale market? Based on a model where oligopolistic pipelines could voluntarily auction gas to competitors (or precommit on certain sales otherwise) we conclude that such release auctions often have no effect because the additional obligations will simply crowd out voluntary sales.
Keywords: 330